Urticaria 2 - Fine, Lauren (Henry Stewart Talks, 2016)
Evaluation & management of urticaria, EAACI and AAAAI guidelines, H1 & H2 antihistamines, Antileukotrienes & glucocorticoids, Specific immune modulating regimens, Duration of treatment, When to refer to an allergist